2017
DOI: 10.1080/17429145.2016.1278049
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of durum wheat (Triticum turgidum L. ssp. durum (Desf.) Husnot) grains with nutrients

Abstract: Durum wheat (Triticum turgidum L. ssp. durum (Desf.) Husnot) was grown under conditions to promote mineral biofortification at the grain level. Along plant development, biomass accumulation and the kinetics of nutrients accumulation were assessed, identifying the nutrient fluxes of roots and shoots, and the timescale constraints of crop biofortification. Plants were grown under environmentally controlled conditions, submitted to four increasing concentrations of nutrient solutions (1-, 2-, 4-and 6-fold) of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Grains were subjected to cyclical analysis through neutron activation (Galinha et al, 2013), being the samples irradiated with a neutron flux of 1.7 × 10 12 cm 2 s −1 , in a fast-pneumatic system. Grain X-ray analysis was done using a Niton Thermal Scientific XLT, as described by Pataco et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…Grains were subjected to cyclical analysis through neutron activation (Galinha et al, 2013), being the samples irradiated with a neutron flux of 1.7 × 10 12 cm 2 s −1 , in a fast-pneumatic system. Grain X-ray analysis was done using a Niton Thermal Scientific XLT, as described by Pataco et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…Foliar application of nutrients is an important crop management strategy to maximize crop yields and concentrations of micronutrients in edible parts. Several studies have demonstrated that foliar application of micronutrients, including Zn and Fe, showed good behavior in increasing their concentration in wheat grain [27,[48][49][50][51][52]. However, little is known about the effect of combined Zn and Fe on the quality of this wheat grain.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen contributes to effective nutrient transport, trafficking, and sequestration. This mechanism supplies trace amounts of nutrients to all cell types at all development stages, which is essential for grain biofortification (Pataco et al, 2017).…”
Section: Introductionmentioning
confidence: 99%